PRINSIP UMUM METODOLOGI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Oby Ara Afima; Sri Murhayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article examines the general principles of Islamic Religious Education (PAI) teaching methodology as a pedagogical and spiritual foundation for shaping students' character. PAI teaching aims not only to transfer religious knowledge but also to instill the values ​​of monotheism, noble morals, and social awareness. This research uses a qualitative approach with a literature review method to analyze relevant literature on learning principles, such as monotheism-based, contextual, holistic, student-centered, and oriented toward developing a profile of a rahmatan lil 'alamin (blessing for the universe) student. The results of the study indicate that PAI teaching methodology must be flexible, integrative, and adaptive to social dynamics and developments. Thus, PAI teaching can be a transformative tool in shaping individuals who are faithful, moral, and able to coexist peacefully in a pluralistic society.